The Effect of Product Quality, Service Quality, and Price on Purchasing Decisions Through Consumer Trust As An Intervening Variable at PT. Freya First Indonusa Medan - Rizki Fajri Nasution; Adelina Lubis; Nur Aisyah (Britain International for Academic Research (BIAR-Publisher), 2025)
This study aims to determine the effect of product quality, service quality, and price on purchasing decisions through consumer trust as an Intervening variable at PT. Freya Frist Indonusa Medan. This study uses independent variables: Product Quality (X1), Service Quality (X2), and Price (X3) dependent variable: Purchase Decision (Y) with intervening variable: Consumer Trust (Z). This study uses quantitative methods, and data collection techniques using questionnaires and observations with structural equation modeling-partial least squares (SEM-PLS) data analysis methods using SmartPLS software. The population in this study was 225 consumers and used the slovin formula technique with a significance level of 0.05, so the number of samples in this study was 144 respondents taken from part of the population. Based on the results of the hypothesis test, Product Quality (X1) has a positive effect on Consumer Trust (Z), with a coefficient value (Original Sample column) = 0.296, and significant, with T-Statistics = 3.486> 1.96 and P-Values ​​= 0.001 <0.05. Service Quality (X2) has a positive effect on Consumer Trust (Z), with a coefficient value (Original Sample column) = 0.304, and significant, with T-Statistics = 3.577> 1.96 and P-Values ​​= 0.000 <0.05. Price (X3) has a positive effect on Purchasing Decisions (Y), with a coefficient value (Original Sample column) = 0.158, and significant, with T-Statistics = 2.263> 1.96 and P-Values ​​= 0.024 <0.05.